Two phased heuristic algorithm for capacitated minimal spanning tree networks. (24th June 2005) - Lee, Yong-Jin
Modern computer networks consist of backbone networks and local access networks. Typical local area networks (LANs) can be defined as end-user-nodes of the local access networks. The problem is composed of finding the best way to link nodes to a central node site and, in graph-theoretical terms, it is to determine a minimal spanning tree with a capacity constraint (CMST). In this paper, a heuristic algorithm with two phases is presented. Computational experience confirms that our algorithm improves the solutions achieved by the existing algorithm and requires the relatively short running time. The algorithm can be applied to design of local area network in an organisation or centralised network.